Electrophysiological characteristics of epicardial breakthrough during catheter ablation of perimitral atrial flutter - Chheng Chhay; Chheng Chhay; Chu-Yu Hsu; Chu-Yu Hsu; Chu-Yu Hsu; Shih-Lin Chang; Shih-Lin Chang; Shih-Lin Chang; Yenn-Jiang Lin; Yenn-Jiang Lin; Yenn-Jiang Lin; Li-Wei Lo; et al. (Frontiers in Cardiovascular Medicine, 2022)
IntroductionUnsuccessful endocardial ablation for perimitral atrial flutter (AFL) could be attributed by the epicardial bridging.ObjectiveThis study aimed to investigate the electrophysiological characteristics of epicardial breakthrough during catheter ablation of perimitral AFL.Materials and methodsThis retrospective study recruited 40 patients who received successful catheter ablation of perimitral AFL from January 2016 to June 2021. The patients were divided into two groups: group 1 (n = 18) successful endocardial ablation, and group 2 (n = 22) successful epicardial ablation following unsuccessful endocardial ablation owing to incomplete mitral block or unachievable termination AFL. The local electrogram (EGM) interval of coronary sinus (CS) duration perimitral AFL was measured before catheter ablation.ResultsThere was no significant difference in the baseline characteristics between the two groups. In group 2, 60% of successful epicardial ablation was performed in intra-CS ablation and 40% in VOM ethanol infusion. Group 2 patients had a longer EGM interval of distal CS than that in group 1 (CS1-2: 64.2 17.5 vs. 42.4 0.09 ms, P = 0.008, CS3-4: 57.13 19.4 vs. 43.8 7.5 ms; P = 0.001). The conduction velocity at successful site was slower in group 2 compared to group 1 (0.18 0.05 vs. 0.75 0.19 m/s, P = 0.040). In the multivariate analysis, distal EGM interval (CS1-2) was identified as independent predictor of the need of epicardial ablation with the optimal cutoff of 49 ms.ConclusionLonger EGM interval in distal CS during perimitral AFL was observed in perimitral AFL patients with epicardial breakthrough following endocardial-failed ablation, which may be associated with the need of epicardial ablation.